The Role of Social Mechanisms in Achieving the Optimal Healing Environment for Oncology Patients Rooms (Adolescents and Young Adults Category-AYA) الاليات الاجتماعية ودورها فى تحقيق البيئة الاستشفائية المثلى لغرف مرضى الأورام فئة المراهقين وصغار البالغين - Hajer Mohamed; Khaled Mohamed Ahmed El-Lithy; Nouby M Hassan (JES: Journal of Engineering Sciences, 2021)
This paper discusses the importance of social mechanisms as one of key elements for achieving optimal healing environment-OHE for oncology patients' rooms, by overviewing the current status of some oncology centers, which focus solely on providing medical treatment without taking into account social, psychological, emotional and spiritual needs of patients, which in turn negatively affect the treatment and recovery of patients, especially adolescents and young adults–AYA, where the challenges of emotional and social resulting from cancer with challenges resulting from adolescence and adulthood. This paper aims to extract social mechanisms for oncology patient rooms, and indicate their role and priorities which will be applied with matching needs of patients of AYA category, mitigating their disorders, and impacts on patients' health outcomes. This paper attempts to reach the best appropriate model to achieve these mechanisms, by analyzing the current situation of selected samples from case study of the South Egypt Cancer Institute in Asyut. Through this analysis, this paper presents a set of results and recommendations that should be followed to develop patient rooms, which take into account the provision of social mechanisms and the implementing priorities depending on impact level of each element in order to reach the suitable setting for the optimal healing environment of the room. This paper relies the analytical descriptive approach to deal with the research problem by revising literature that dealt with the characterization and analyzing the needs of AYA oncologists in patient rooms, identifying the disorders and effects of the disease on this category, then identifying the appropriate social mechanisms that can be match their needs in the rooms. An analytical and deductive approach is followed through implementing various research tools and procedures to analyze the coverage of current status to know how these mechanisms are achieved within different models of patient rooms and how they affect patient health, then to analyze data and outcomes results. Finally, this paper concludes with a comprehensive chart of social mechanisms’ matrix suitable for optimal healing environment in AYA patients’ rooms. تناقش الورقة البحثية أهمية الآليات الاجتماعية کأحد العناصر الأساسية لتحقيق منظومة البيئة الاستشفائية المثلى لغرف مرضى الأورام، فمن خلال دراسة واقع بعض مراکز علاج الأورام تبين أنها ترکز على تقديم العلاج الطبي فقط دون الأخذ في الاعتبار تلبية الاحتياجات الاجتماعية والنفسية والعاطفية للمرضى بما يؤثر سلباً على علاج المرضى وسرعة الشفاء خاصة فئة المراهقين وصغار البالغين، حيث تتداخل التحديات العاطفية والاجتماعية الناتجة عن المرض مع تحديات مرحلة المراهقة والبلوغ. تهدف الورقة البحثية إلى استخلاص الآليات الاجتماعية (کأحد آليات تحقيق البيئة الاستشفائية المثلى) لغرف مرضى الأورام، وبيان دورها وأولويات تطبيقها في تلبية احتياجات المرضى فئة المراهقين وصغار البالغين، والتخفيف من اضطراباتهم، وتقييم الوضع الراهن للبيئة المبنية لمعرفة مدى تحقيق هذه الآليات.